PENGARUH VOLUME PERDAGANGAN SAHAM, LEVERAGE, DAN TINGKAT SUKU BUNGA TERHADAP VOLATILITAS HARGA SAHAM - Krisna Dewi, Ni Made Ayu; Suaryana, I Gst Ngr Agung (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of the volume of stock trading, leverage, and the interest rate on stock price volatility. This research was conducted at the Indonesian Stock Exchange by selecting a sample of companies listed in the LQ 45 in 2010 to 2014. The population in this study as many as 45 companies and a total sample of 18 companies selected to pass through purposive sampling phase, so that the number of sample observations for 5 years to 90 samples. The analysis technique used in this research is multiple linear regression. The results of this study indicate that the volume of stock trading positive effect on stock price volatility due to the information received by market participants come from pergadangan volume stocks. This shows that the higher the trading volume, the higher the volatility of stock prices, while leverage and interest rates do not affect the stock price volatility.
Keywords: Volatilitas Harga Saham, Volume Perdagangan Saham, Leverage, Tingkat Suku Bunga